Development and validation of spectrophotometric method for the determination of meldonium dihydrate in dosage forms - Donchenko, Аnastasiia; Nahorna, Natalia; Vasyuk, Svitlana (ScienceRise: Pharmaceutical Science, 2018)
Aim. Spectrophotometry is one of the most widely used methods in the pharmaceutical analysis. The main advantages of this absorption method are the highly sensitive, cost-effective and available to quality control laboratories for dosage forms. However, there is a need to find new analytical reagents. Therefore, the aim of the present work was investigation and development of spectrophotometric method based on reaction with p-chloranil for the determination of meldonium dihydrate in dosage forms. Methods. In the study were used working standard of meldonium dihydrate, p-chloranil, DMF, the sample of finished dosage forms. Absorption of the reaction products was measured using spectrophotometer Specord 200. Results. The optimum conditions of the spectrophotometric analysis has been established during the process of development this procedure. The influence of various parameters such as nature of the solvent, concentration of reagent, temperature, time of heating were investigated. It was experimentally established that meldonium dihydrate reacts with p-chloranil in DMF medium to form the coloured reaction product with absorption maximum at 556 nm. The proposed method was subjected to validation tests. The method was validated for the parameters like linearity, precision, accuracy, robustness and range of application. Beer’s law was performed at the concentration range of 8.00-20.00 mg/100 ml with correlation coefficient 0.9995. The linearity ranges were calculated with the help of regression analysis by means of least squares. The proposed procedure meets the requirements of State Pharmacopoeia of Ukraine. Conclusions. The spectrophotometric method for the determination of meldonium dihydrate was developed and validated. This procedure is successfully applied for dosage forms analysis. Results of the study showed that the procedure is accurate, simple and relevant for application at the quality control laboratories for dosage forms